Pengaruh Lupene-ol dan Lupene-on dari Aegle marmelos Correa terhadap Pelepasan Enzim β-hexoaminidase dari Sel Mast - AGUNG ENDRO NUGROHO; SUGENG RIYANTO; MOHAMAD ASPOLLAH SUKARI; KAZUTAKA MAEYAMA (Fakultas Farmasi Universitas Pancasila, 2010)
20(29)-lupene-3α-ol and 20(29)-lupene-3-on are pentacyclic triterpenes isolated from Aegle marmelos Correa collected in Yogyakarta, Indonesia. Their molecular structures were confirmed in Universiti Putra Malaysia. These compounds were obtained from petroleum ether extract of the plant’s stem bark. This study investigated the effects of the compounds on the β -hexoaminidase enzyme release from mast cell culture (RBL-2H3 cell line). DNP24-BSA was used as immunologic inducer for the β -hexoaminidase release from the mast cells. The enzyme release was determined by colorimetric methods with a substrate, p-nytrophenyl-2-acetamydo-2-deoxy- β -D-gluko-pyranocide, and a microplate reader at 405 nm. lt was found that treatment with 20 µg/ml DNP24-B SA could stimulate the release of β -hexoaminidase from RBL-ZH3 cells by 3O.83 ± 1.10%. Lupene-ol and lupene-on showed inhibitory effects on the β -hexoaminidase release from RBL-2H3 cells induced by DNP24-BSA in dose-dependent manner. At the dose of 100 µM, lupene-ol and lupene-on inhibited the β -hexoaminidaserelease by 35.69i4.7 5% and 39.19 9.56%, respectively. The ICN values of their effects on DNP24-BSA experiments were 59.40 µM and 72.51 µM. The results suggested that the inhibitory effect of lupene-ol and lupene-on on the β-hexoaminidase release involved mechanisms related to the interaction of IgE on the RBL-2H3 cells surface or intracellular signal transductions found in the mast cell degranulation. Key words: Aegle marmelos Correa, lupene-ol, lupene-on, mast cells, β -hexoaminidase enzyme.